Investigação da atividade antifúngica e anti-biofilme de 2-cloro-n-fenilacetamida sobre Candida albicans e Candida parapsilosis resistentes ao fluconazol - Diniz Neto, Hermes (2022)
Infections caused by the Candida genus, especially systemic ones, represent a challenge for public health due to high morbidity and mortality, high associated costs and difficulty in treatment with a good clinical prognosis. Candida albicans is the most frequent cause of this infection, however, the number of cases caused by non-albicans species such as C. parapsilosis has emerged, with a remarkable record of resistant strains. The search for new therapeutic alternatives becomes an important resource in the control of these infections and the use of some already known substances, such as 2-chloro-N-phenylacetamide, is a way to obtain potentially effective new products. Therefore, the antifungal potential of 2-chloro-N-phenylacetamide was investigated against fluconazole-resistant C. albicans and C. parapsilosis strains. The antifungal activity of 2-chloro-N-phenylacetamide was evaluated in vitro by the determination of the minimum inhibitory and fungicidal concentrations (MIC and MFC), inhibition of biofilm formation and its rupture, investigation of the possible mechanism of action, and association between this molecule and amphotericin B and fluconazole. The test product inhibited all strains of C. albicans and C. parapsilosis, with a MIC ranging from 128 to 256 μg.mL-1, and a MFC of 512 to 1,024 μg.mL-1. It also inhibited up to 92% of biofilm formation and rupture of up to 87% of preformed biofilm. However, 2-chloro-N-phenylacetamide did not promote antifungal activity by binding to cell membrane ergosterol, nor did it impair the integrity of the fungal cell wall. Antagonism has been observed when combining this substance with amphotericin B and fluconazole. The substance exhibited significant antifungal effects by inhibiting both planktonic cells and the biofilm of fluconazole-resistant strains. It is worth noting that its combination with other antifungals should be avoided and that its mechanism of action remains to be established.